Pelaksanaan Kurikulum 2013 Terhadap Mata Pelajaran Geografi di SMA Negeri 11 Makassar - Jumrina, Jumrina (LaGeografia, 2018)
This study aims to determine the application of the 2013 curriculum which can be seen from: 1) the teaching learning process viewed from the scientific approach. This research uses descriptive quantitative, data collection is done by using questionnaire techniques, interviews and observations. This sample is for all geography teachers at SMAN 11 Makassar. The data collected was analyzed using percentages. The results of the study showed that the Geography teacher of Makassar State High School had understood all the applicable rules, but the implementation of the teaching learning process activities had been carried out but was still not effective in implementing the scientific approach.